ANALYSIS OF BUSINESS DEVELOPMENT BASED ON MANGROVE IN THE DAMAS BEACH DISTRICT TRENGGALEK - pudji purwanti; edi susilo; dwi setijawati (Journal of Innovation and Applied Technology, 2016)
Mangrove forests in Damas coastal has many switching function as plantations, causing a reduction in mangrove forest areas. The decline in mangrove forest area as a result of conversion to palm plantation committed by some members of the group LMDH "Agro Lestari". This is due to the assumption of palm trees have economic value that is higher than the mangrove vegetation. Meanwhile, mangrove forest conservation efforts have been carried out by the service related to the bakau’s management group or Pokmaswas (Community Monitoring Group) called "Anchor Marine". However, the efforts of mangrove reforestation were less successful, due to the conversion of mangrove land for palm plantations is still running.This study evaluates the implementation of awareness activities in the management of mangrove forests and mangrove-based business training activities. Based on the evaluation of activities after the extension, shows that people have a positive behavior and participation of the management of mangrove forests. Based on the evaluation results to the participants counseling and training mangrove processing, respondents are interested in developing mangrove syrop (80%), crackers mangrove (70%) and brownies (60%). Based on the respondent's ability to perform processing as much as 60% of respondents feel they have the ability in processing dodol, and 60% of respondents also feel have the ability in processing syrop mangrove. Based on the analysis of business profitability, the development of products brownies value profitability 47.26%, while the mangrove crackers 43.41% and 46.93% dodol mangrove. While syrop pepada has a profitability of 16.35%. Making api-api brownies, api-api crackers and api-api dodol can be done when the fruit season fires for 4 months.